Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content: 1. Achieving a chapter (In combination with travel and rain) in the Sunni talents book Explanation of the urban introduction of Sheikh Said Baishen (Verification and Annotation) Mr. Saleh Abdoalgaader Ali Bahomaid 2. Electronic banking services their means and jurisprudential rulings Dr. Abdellatif Elkhayali bin Mohammed 3. The Hadiths on Rising for Funeral among the Hadith Scholars and Jurists (Fuqaha): An Applied Study from the Book (Sunna Abo Dawood) Mr. Abdullah Salem Abuftaim 4. Consumer rationalization in the Sunnah of the Prophet: An objective study Dr. Mohamed Zaher Alzahran 5. The purpose of the woman’s covering and preservation and its impact on the rulings of Hajj (As a model) Ms. Najla Mohammed Burhan Mohammed Nour, Co-Prof. Nada Turki Al-Moqbel 6. Mental Fundamentals Role in Islamic Studies: Fundamental and Comparative Study Mr. Mohamad Mostafa Charmand